Macrophage GSK3β-deficiency inhibits the progression of hepatocellular carcinoma and enhances the sensitivity of anti-PD1 immunotherapy. Issue 12 (20th December 2022) - Sun, Guangshun; Liu, Hanyuan; Zhao, Jie; Zhang, Jinyu; Huang, Tian; Sun, Guoqiang; Zhao, Siqi; Zhang, Zihao; Cao, Hengsong; Rong, Dawei; Kong, Xiangyi; Ji, Qinghua; et al.
Abstract : Background: Glycogen synthase kinase 3β (GSK3β) was originally discovered to regulate glycogen synthesis and show a relationship to tumors. However, the biological functions of GSK3β in tumor-associated macrophages (TAMs) in cancers including hepatocellular carcinoma (HCC) remain unclear. Methods: The enrichment of GSK3β in tumor tissues was assessed by Gene Expression Omnibus (GEO) database. The in vitro and in vivo assays assisted in evaluating how GSK3β in TAMs affected HCC in terms of proliferation, invasion and migration. Immunofluorescence was used to assess GSK3β expression in TAMs in the anti-PD1 therapy non-responsive HCC group and the responsive group. Western blot and coimmunoprecipitation were performed to demonstrate the interaction between GSK3β and PD-L1. We carried out in vivo experiments in a C57BL/6 mouse model of HCC established through subcutaneous injection. Results: GEO single-cell RNA sequencing data suggested that GSK3β was highly enriched in TAMs of HCC. According to in vitro and in vivo experiments, reducing GSK3β in TAMs inhibits the cancer cell proliferation, invasion, and migration. The immunofluorescence and immunohistochemistry results confirmed that the GSK3β is significantly upregulated in TAMs of the anti-PD1 therapy non-responsive group in comparison with the responsive group. In vitro and in vivo experiments confirmed that reduced GSK3β in TAMs are capable of enhancing the sensitivity of anti-PD1 immunotherapy for HCC by decreasing PD-L1 ubiquitination. Mass spectrometry results suggested that high expression of CD14 + GSK3β + in the peripheral blood mononuclear cell (PBMC) can predict non-responsive to anti-PD1 treatment. Moreover, escitalopram is confirmed to act as GSK3β inhibitor that can increase the sensitivity of anti-PD1 immunotherapy for HCC. Conclusions: This study revealed that macrophage GSK3β deficiency can inhibit the development of HCC by inhibiting the M2 phenotype and enhance the sensitivity of anti-PD1 immunotherapy for HCC by decreasing PD-L1 ubiquitination. The expression of CD14 + GSK3β + in PBMC can noninvasively predict anti-PD1 sensitivity in HCC patients, which provides novel strategies to predict anti-PD1 sensitivity, increase anti-PD1 therapeutic effect, and bring new hope for HCC patients.